Biochemistry of the cingulate cortex in autism: An MR spectroscopy study. Issue 6 (3rd November 2015) - Libero, Lauren E.; Reid, Meredith A.; White, David M.; Salibi, Nouha; Lahti, Adrienne C.; Kana, Rajesh K.
Abstract : Neuroimaging studies have uncovered structural and functional alterations in the cingulate cortex in individuals with autism spectrum disorders (ASD). Such abnormalities may underlie neurochemical imbalance. In order to characterize the neurochemical profile, the current study examined the concentration of brain metabolites in dorsal ACC (dACC) and posterior cingulate cortex (PCC) in high‐functioning adults with ASD. Twenty high‐functioning adults with ASD and 20 age‐and‐IQ‐matched typically developing (TD) peers participated in this Proton magnetic resonance spectroscopy (1H‐MRS) study. LCModel was used in analyzing the spectra to measure the levels of N‐Acetyl aspartate (NAA), choline (Cho), creatine (Cr), and glutamate/glutamine (Glx) in dACC and PCC. Groups were compared using means for the ratio of each metabolite to their respective Cr levels as well as on absolute internal‐water‐referenced measures of each metabolite. There was a significant increase in Cho in PCC for ASD adults, with a marginal increase in dACC. A reduction in NAA/Cr in dACC was found in ASD participants, compared to their TD peers. No significant differences in Glx/Cr or Cho/Cr were found in dACC. There were no statistically significant group differences in the absolute concentration of NAA, Cr, Glx, or NAA/Cr, Cho/Cr, and Glx/Cr in the PCC. Differences in the metabolic properties of dACC compared to PCC were also found. Results of this study provide evidence for possible cellular and metabolic differences in the dACC and PCC in adults with ASD. This may suggest neuronal dysfunction in these regions and may contribute to the neuropathology of ASD. Autism Res 2016, 9: 643–657 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.